2022
DOI: 10.1126/science.abm1670
|View full text |Cite
|
Sign up to set email alerts
|

Compartment-specific tuning of dendritic feature selectivity by intracellular Ca 2+ release

Abstract: Dendritic calcium signaling is central to neural plasticity mechanisms that allow animals to adapt to the environment. Intracellular calcium release (ICR) from the endoplasmic reticulum has long been thought to shape these mechanisms. However, ICR has not been investigated in mammalian neurons in vivo. We combined electroporation of single CA1 pyramidal neurons, simultaneous imaging of dendritic and somatic activity during spatial navigation, optogenetic place field induction, and acute genetic augmentation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 84 publications
6
74
0
Order By: Relevance
“…Although backpropagating action potentials may contribute to the dendritic Ca 2+ signal recorded in our study, we suggest that they do not drive the compartmentalized increase in Ca 2+ signaling within tuft dendrites as we would expect to see a similar change in the Ca 2+ response in basal dendrites, which was not the case. Our findings further suggest that intracellular calcium stores also did not primarily drive the changes in dendritic Ca 2+ responses, as fear learning did not alter the spatial pattern of dendritic activity which has recently been shown to be influenced by intracellular calcium release ( O'Hare et al, 2022 ). Additional in-depth experiments are required to determine the presynaptic and/or postsynaptic modifications which drive the reported changes in dendritic signaling following fear learning, which is an exciting new avenue for future research.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Although backpropagating action potentials may contribute to the dendritic Ca 2+ signal recorded in our study, we suggest that they do not drive the compartmentalized increase in Ca 2+ signaling within tuft dendrites as we would expect to see a similar change in the Ca 2+ response in basal dendrites, which was not the case. Our findings further suggest that intracellular calcium stores also did not primarily drive the changes in dendritic Ca 2+ responses, as fear learning did not alter the spatial pattern of dendritic activity which has recently been shown to be influenced by intracellular calcium release ( O'Hare et al, 2022 ). Additional in-depth experiments are required to determine the presynaptic and/or postsynaptic modifications which drive the reported changes in dendritic signaling following fear learning, which is an exciting new avenue for future research.…”
Section: Discussionsupporting
confidence: 59%
“…Such changes were not observed in basal dendrites, suggesting learning-related neuronal compartmentalization of dendritic plasticity. This dendrite-specific plasticity is not unique to cortical pyramidal neurons as recent studies have also reported compartmentalized plasticity in the lateral amygdala ( d'Aquin et al, 2022 ) and hippocampus ( O'Hare et al, 2022 ). Taken together, these results illustrate that neurons are multicompartmental ( Häusser and Mel, 2003 ) which, by providing neurons with multiple independent integrative units that process information in parallel, increases the computational power of a single neuron ( Poirazi et al, 2003 ; Jadi et al, 2014 ; Ujfalussy et al, 2018 ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As MERCs mediate ER-to-mitochondria calcium transfer, and loss of Pdzd8 increases intracellular calcium dynamics in mouse neurons ( O’Hare et al, 2022 ), we next explored whether calcium handling was altered in this AD model. Functional mitochondria can take up substantial amounts of calcium released from the ER before exceeding their so-called calcium retention capacity (CRC).…”
Section: Resultsmentioning
confidence: 99%
“…The reversal of ion fluxes near synapses is thought to account for a large fraction of the neuron’s energy budget (Attwell and Laughlin, 2001; Harris et al, 2012), and mitochondrial densities weakly correlate with synaptic densities in the dendrites of mouse cortical pyramidal neurons (Turner et al, 2022). Mitochondria also buffer calcium (Werth and Thayer, 1994), and variations in mitochondrial densities may contribute to compartment-dependent differences in calcium buffering capacities, which have recently been shown to contribute to place field formation in awake and behaving mice (O’Hare et al, 2022).…”
Section: Discussionmentioning
confidence: 99%